(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
The integration of AI-powered tools in teacher education is revolutionizing the way pre-service English teachers develop critical thinking skills. AI-driven applications such as intelligent tutoring systems, adaptive learning platforms, and automated feedback mechanisms provide personalized learning experiences that encourage analytical reasoning and problem-solving. This article examines the opportunities AI presents in fostering critical thinking, including real-time feedback, interactive discussions, and tailored learning pathways. However, it also addresses key challenges such as ethical concerns, algorithmic biases, and accessibility issues. The study highlights best practices for integrating AI effectively in teacher training programs, ensuring that it complements rather than replaces traditional pedagogical approaches. Findings suggest that while AI has immense potential to enhance critical thinking, its implementation must be carefully designed to maintain human-centered teaching values. The article concludes by discussing the implications of AI in shaping future educators’ competencies and readiness for dynamic classroom environments.